2007
DOI: 10.3200/socp.147.3.285-298
|View full text |Cite
|
Sign up to set email alerts
|

Jurors' Locus of Control and Defendants' Attractiveness in Death Penalty Sentencing

Abstract: The authors examined the relationship between jurors' locus of control and defendants' attractiveness in death penalty sentencing. Ninety-eight participants voluntarily served as mock jurors. The authors administered J. B. Rotter's (1966) Internal-External Locus of Control Scale to participants and then randomly assigned them to a group with either an attractive or an unattractive defendant (represented by photographs). Participants read a murder vignette and selected a punishment--either a lifetime jail sente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The effect of physical appearance on differential treatment has been a frequent subject of psychological research (Feingold, 1992;Beckham et al, 2007;Jonason, 2009). However, empirical studies of its impact on employee turnover, particularly among female auditors, are rare.…”
Section: Physical Appearancementioning
confidence: 99%
“…The effect of physical appearance on differential treatment has been a frequent subject of psychological research (Feingold, 1992;Beckham et al, 2007;Jonason, 2009). However, empirical studies of its impact on employee turnover, particularly among female auditors, are rare.…”
Section: Physical Appearancementioning
confidence: 99%
“…Overall, then, the attraction-leniency bias has been shown to operate across decision makers (judges and jurors), types of crime, and trial type (criminal and civil), albeit it is moderated by the seriousness of the crime (Beckham & Spray & Pietz, 2007) and the strength of evidence against the defendant (Erian et al, 1998). 2 In view of evidence that jurors are, at least occasionally, influenced by extralegal factors and at times give improper weight to such factors in their decision-making, one might ask whether certain personality types might be more susceptible to extralegal influences of the type described above.…”
Section: The Attraction Leniency Biasmentioning
confidence: 99%
“…In negligent homicide cases, both physically attractive and unattractive defendants were declared guilty at equal rates; however, when they were sentenced, physically attractive defendants were sentenced more leniently than unattractive defendants (Landy and Aronson, 1969). Other scholars have suggested that observations of the attraction-leniency effect are limited to less severe and victimless offenses (Downs and Lyons 1991, Mazzella and Feingold 1994, Beckham et al 2007. After applying more realistic jury simulations or controlling for seriousness of crime and race, the effects of physical attractiveness on legal leniency disappear altogether (Weiten 1994, Kutys 2013.…”
Section: Angels and Demons In Front Of The Jurymentioning
confidence: 99%